Trends in Early Discharge and Associated Costs after Transcatheter Aortic Valve Replacement: A National Perspective. Issue 4 (July 2021) - Okoh, Alexis K.; Siddiqui, Emaad; Soto, Cassandra; Dhaduk, Nehal; Hirji, Sameer; Tayal, Rajiv; Chen, Chunguang; Lee, Leonard Y.; Russo, Mark J.
Objective: The current study aims to report trends of early discharges and identify associated direct costs using a nationally representative database of real-world data experience. Methods: We used nationally weighted data on all patients who had transfemoral transcatheter aortic valve replacement (TAVR) from 2012 to 2017 and discharged alive from the National Inpatient Sample. Patients were divided into early (discharge ≤3 days of admission) and late discharge. Demographics and clinical characteristics were compared. Trends in early discharge and costs associated with admissions were analyzed over the study period. Results: Of the 125, 188 patients identified, 59, 424 (46.9%) were discharged early. The proportion of early discharge increased from 15% in early 2012 to 68% in late 2017 ( P < 0.001), with the largest increase occurring from 2014 to 2015. Overall, the average cost of TAVR decreased from $58, 408 in 2012 to $49, 875 in 2017 ( P < 0.001). Compared to late discharge, patients discharged early reported costs savings of ≥$20, 000 over the study period. Among the early discharge group, no significant differences in costs were observed for patients discharged on 0 to 1, 2, or 3 days after the procedure. Conclusions: Postoperative length of stay after TAVR has decreased dramatically within the last decade with an observed reduction in procedural costs. While discharge within 3 days appeared cost effective, no differences in costs were noted among patients discharged ≤3 days.